Eliminating dog-mediated rabies: challenges and strategies - Harish Kumar Tiwari; Jully Gogoi-Tiwari; Ian D. Robertson (BMC, 2021)
Abstract Rabies is an acute encephalitis caused by a lyssavirus. It is primarily transmitted through bites of infected dogs which results in the worldwide death of an estimated 59000 humans every year. The disease is preventable through the application of post-exposure prophylaxis (PEP) and its elimination has been demonstrated in many countries by applying multiple interventions simultaneously. Nonetheless, rabies is still widespread in many developing countries, primarily due to the poor implementation of intervention strategies that include inadequate dog-bite wound management practices, unavailability/unaffordability of PEP by the communities, failure to control the disease in free-roaming dogs and wildlife, improper dog population management, weak surveillance and diagnostic facilities and a lack of a One Health approach to the disease. In this review, strategies to control dog-mediated rabies through a One Health approach were discussed. We recommend applying multiple interventions against the disease by involving all the concerned stakeholders in selected urban and rural areas of the countries where rabies is endemic. An empirical demonstration of disease freedom in the selected areas through a One Health approach is needed to convince policymakers to invest in rabies prevention and control on the national level. This multifaceted One Health control model will enhance the likelihood of achieving the goal of global rabies eradication by 2030.